Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208543
|View full text |Cite
|
Sign up to set email alerts
|

Biometric-rich gestures

Abstract: In this paper, we present a novel multi-touch gesture-based authentication technique. We take advantage of the multitouch surface to combine biometric techniques with gestural input. We defined a comprehensive set of five-finger touch gestures, based upon classifying movement characteristics of the center of the palm and fingertips, and tested them in a user study combining biometric data collection with usability questions. Using pattern recognition techniques, we built a classifier to recognize unique biomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…Such a modular approach allows for coverage of a wide span of input methods and technologies starting with traditional mouse-based input and its enhancements with gesture dynamics [2], going through classic 2-DOF digitizers, tablets, and sign pads for 2D graphical input and their enhanced multiple-DOF versions capable to track the stylus azimuth, elevation, and applied forces [3]. We also cover current touch screen based input both for singleand multi-touch surfaces [4]. While there are many applications that employ tablets and electronic sign pads to authorize access to bank accounts or credit card purchases, they are all limited to obtaining a user signature on a specialized flat surface [5].…”
Section: Framework Building Blocks and Componentsmentioning
confidence: 99%
“…Such a modular approach allows for coverage of a wide span of input methods and technologies starting with traditional mouse-based input and its enhancements with gesture dynamics [2], going through classic 2-DOF digitizers, tablets, and sign pads for 2D graphical input and their enhanced multiple-DOF versions capable to track the stylus azimuth, elevation, and applied forces [3]. We also cover current touch screen based input both for singleand multi-touch surfaces [4]. While there are many applications that employ tablets and electronic sign pads to authorize access to bank accounts or credit card purchases, they are all limited to obtaining a user signature on a specialized flat surface [5].…”
Section: Framework Building Blocks and Componentsmentioning
confidence: 99%
“…A touch screen authentication system has been developed in (Sae-Bae, Ahmed, Isbister, & Memon, 2012 They also have shown that user defined gestures present better results than the supplied ones. The same conclusion has been confirmed in (Sherman et al, 2014) through the use of free-form gesture in the authentication system.…”
Section: ) Hand Gesturesmentioning
confidence: 99%
“…The other method by Sae-Bae et al [10] is almost the same as a method by Iseri et al The method by Sae-Bae et al requires a big screen such as a screen on a 10 inch tablet.…”
Section: Related Workmentioning
confidence: 99%
“…The difference of the right side of equations (8) and (9) is FS i . When users are standing on a stable floor and holding their smart phones, values are acquired as shown in Equation (10).…”
Section: Absorption Of Influence Of Floor Shakementioning
confidence: 99%